Peningkatan Kinerja Perpustakaan Melalui Penerapan Sistem Knowledge - Rizqy Alfiansyah, Rafif; Octavia Rahmawati, Anin; Hafid Krisna Wahyu Wijaya, Muhammad; Farid Faqih, Muhammad; Rhemadanu, Andreas; Nurjanah, Umi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This research focuses on improving library performance through the implementation of an information-based system. The system is designed to help libraries manage information resources more effectively, enhance accessibility, and support learning and research processes. The research methods include problem identification, literature review, knowledge-based system design, and prototype evaluation before full implementation. The benefits of implementing this system include increased operational efficiency, improved service quality, support for learning and research, knowledge management, and information literacy. The data model used applies case-based techniques with similarity calculations between user needs and the information of the books owned, involving features such as genre and publication year. The similarity calculation results are used to provide book recommendations to library visitors. For example, the system recommends the book "To Kill a Mockingbird" because it shares the same genre and publication year as "The Alchemist". Process modeling has proven to be an essential tool in developing an effective and efficient system. This research also includes relevant references to support the findings and methodologies used.